Mycotic aneurysm of the hepatic artery in pediatric liver transplantation: A case series and literature review. Issue 3 (13th March 2018) - Camagni, S.; Stroppa, P.; Tebaldi, A.; Lucianetti, A.; Pinelli, D.; Pellicioli, I.; D'Antiga, L.; Colledan, M.
Abstract: Mycotic aneurysm of the hepatic artery (HA) is a rare, unpredictable, and potentially lethal complication of liver transplantation (LT). Pediatric LT is not exempt from it but the related literature is rather scanty. We present our experience with post‐LT mycotic aneurysm of the HA in pediatric age, describing four cases occurred with a special focus on the possible risk factors for its development and a proposal for the management of high‐risk recipients.